2021
DOI: 10.2196/24363
|View full text |Cite
|
Sign up to set email alerts
|

eHealth Applications to Support Independent Living of Older Persons: Scoping Review of Costs and Benefits Identified in Economic Evaluations

Abstract: Background eHealth applications are constantly increasing and are frequently considered to constitute a promising strategy for cost containment in health care, particularly if the applications aim to support older persons. Older persons are, however, not the only major eHealth stakeholder. eHealth suppliers, caregivers, funding bodies, and health authorities are also likely to attribute value to eHealth applications, but they can differ in their value attribution because they are affected different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 82 publications
1
33
0
2
Order By: Relevance
“…In response to the pandemic, the Centers for Medicare and Medicaid Services (CMS) and private insurers expanded coverage for both video and phone telehealth visits, and telemedicine utilization increased exponentially [3][4][5] and expanded into primary care [6,7]. While further study is needed to explore the challenges of telemedicine [8], initial studies have found that with certain patient populations and conditions, telemedicine is associated with a number of patient and clinician benefits, including reduced appointment wait times, costs, improved medication adherence and blood pressure control, and high rates of patient and clinician satisfaction [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In response to the pandemic, the Centers for Medicare and Medicaid Services (CMS) and private insurers expanded coverage for both video and phone telehealth visits, and telemedicine utilization increased exponentially [3][4][5] and expanded into primary care [6,7]. While further study is needed to explore the challenges of telemedicine [8], initial studies have found that with certain patient populations and conditions, telemedicine is associated with a number of patient and clinician benefits, including reduced appointment wait times, costs, improved medication adherence and blood pressure control, and high rates of patient and clinician satisfaction [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The global increase in the proportion of older adults is therefore expected to significantly increase global health care usage and costs [6]. To keep the health care system sustainable in the future, governments and societies are considering technology as a promising solution for health service delivery innovation and for service expansion without increasing human resource capacity [7][8][9]. Moreover, the COVID-19 outbreak has had extensive consequences for the provision of health care.…”
Section: Introductionmentioning
confidence: 99%
“…Reimbursement is mentioned as a solution—‘a suitable reimbursement solution should be adopted24’—or as a barrier: ‘there is no financial backing to adopt new systems such as remote monitoring’ 40. Economic evaluations of eHealth applications are gaining momentum, and studies have shown considerable variation regarding the costs and benefits that they include 42. Economic studies on telemonitoring in heart failure and women at risk of pre-eclampsia describe this duality.…”
Section: Discussionmentioning
confidence: 99%